Enhanced superconducting qubit performance through ammonium fluoride etch - Cameron J Kopas; Dominic P Goronzy; Thang Pham; Carlos G Torres Castanedo; Matthew Cheng; Rory Cochrane; Patrick Nast; Ella Lachman; Nikolay Z Zhelev; André Vallières; Akshay A Murthy; Jin-su Oh; et al. (Materials for Quantum Technology)
The performance of superconducting qubits is often limited by dissipation and two-level systems (TLS) losses. The dominant sources of these losses are believed to originate from amorphous materials and defects at interfaces and surfaces, likely as a result of fabrication processes or ambient exposure. Here, we explore a novel wet chemical surface treatment at the Josephson junction-substrate and the substrate-air interfaces by replacing a buffered oxide etch (BOE) cleaning process with one that uses hydrofluoric acid followed by aqueous ammonium fluoride. We show that the ammonium fluoride etch process results in a statistically significant improvement in median $\text{T}_1$ by $\sim22%$ ( p = 0.002), and a reduction in the number of strongly-coupled TLS in the tunable frequency range. Microwave resonator measurements on samples treated with the ammonium fluoride etch after niobium deposition and etching also show $\sim33%$ lower TLS-induced loss tangent compared to the BOE treated samples. As the chemical treatment primarily modifies the Josephson junction-substrate interface and substrate-air interface, we perform targeted chemical and structural characterizations to examine materials differences at these interfaces and identify multiple microscopic changes that could contribute to decreased TLS losses.